Benefits of measurable population connectivity metrics for area-based marine management. (October 2022) - Krueck, Nils C.; Tong, Colm; Cox, Courtney; Treml, Eric A.; Critchell, Kay; Chollett, Iliana; Adhuri, Dedi S.; Beger, Maria; Muenzel, Dominic; Holstein, Daniel; Campbell, Stuart J.; Jakub, Raymond
Abstract: The dispersal of larvae by ocean currents is likely to represent an increasingly important driver of marine population dynamics across fragmented habitats. A boost in availability of larval dispersal data from biophysical simulations has therefore led to routine calculations of population connectivity metrics that are used for area-based management decision support, including the placement of Marine Protected Areas (MPAs). However, connectivity-based decision support for area-based management is often complex, highly uncertain, and the associated conservation impact rarely if ever evaluated. In combination, these challenges risk stakeholder engagement, compliance, and overall management effectiveness. Here we use a case study representing multiple key fishery species on coral reefs in Indonesia to demonstrate that consideration of larval dispersal for MPA placement decision support could be critical to recover both fish populations and fisheries from depletion, thereby mitigating potentially severe impacts on coastal communities. Importantly, we further show that MPA placement decisions can be effective even if based on comparatively simple and empirically measurable dispersal characteristics. Maximizing larval export, expressed as the contribution of larvae from MPA candidate sites to total larval settlement in surrounding areas, for example, was found to be a broadly beneficial MPA placement prioritization approach. Across investigated fish families with diverse life histories, this strategy resulted in MPA network designs that increased catches by a factor of 1.3 ± 0.3 (mean ± SD) and total fish biomass by a factor of 3.2 ± 0.3 (9.7 ± 1.2 in no-fishing areas and 1.4 ± 0.3 in fished areas) compared to conditions without effectively managed or protected areas. Our findings are relevant for both the implementation and impact evaluation of global marine conservation policies, specifically in tropical biodiversity hotspots, such as Indonesia, where coral reefs are often overfished and increasingly threatened but local communities highly dependent on sustainable fisheries. Highlights: Connectivity via larval dispersal is a likely driver of marine population dynamics. Area-based management should consider connectivity to support positive outcomes. Connectivity metrics need to be simple and measurable to ensure positive impact. Simply maximizing larval export meets key conservation and fisheries objectives.